Exploring teachers' strategies in planning in-depth learning of science in junior high school - Kawit Sayoto; Enung Hasanah; Muhammad Zuhaery; Russasmita Sri Padmi (Universitas Ahmad Dahlan, 2026)
This study aims to construct an effective deep science learning planning model for junior high school teachers on the topic of living systems and cells, focusing on teacher perceptions, student readiness, and the instructional challenges encountered. A descriptive qualitative method was employed, involving in-depth interviews with science teachers and a document study of instructional plans. The findings reveal that deep science learning planning model is contingent upon a fundamental transformation of the teacher’s role into an instructional orchestrator who integrates spiritual dimensions as substantive learning outcomes. While students exhibited metacognitive gaps in navigating experimental inquiry, the study highlights the efficacy of faded scaffolding strategies and virtual laboratory integration in enhancing student self-efficacy amidst resource constraints. The research concludes that despite the systemic tension between time-intensive inquiry and standardized assessments, the adaptation of flexible scaffolding is crucial for bridging scientific reasoning with national testing policies. These results corroborate existing frameworks on deep learning while providing a practical model for teachers in constructing self-identity through an awareness of the Creator’s design in science.